Fragment d'un homiliari amb dos sermons de Màxim de Torí (s. XII-XIII) (Guissona, Arx. Mun., frag. s/n) - Alturo i Perucho, Jesús (Miscel·lània litúrgica catalana, 2012)
The article aims to present a new codex fragment today preserved in the Guissona Municipal Archive, s/n, copied in the 12-13th century with proto-gothic scripture, probably at La Seu dUrgell. The fragment contains two sermons by Maximus of Turin, the rests of an Homiliary of Roman type, with some textual variants here indicated.